Efeito de drogas utilizadas no tratamento de hipertensão arterial sistêmica sobre a pressão intra-ocular: Estudo experimental no cão - Hashimoto, Mitsuo [UNESP]; De Moraes Silva, Maria Rosa Bet [UNESP]; Teixeira Neto, Francisco José [UNESP] (FapUNIFESP (SciELO), 2002)
Purpose: To study the effects of two drugs (captopril and propranolol) used in the treatment of systemic hypertension, on the intraocular pressure (IOP) of anesthetized dogs. Methods: 24 dogs, divided into 3 groups of 8 each. In the first group, 1.5 mg/kg IV of captopril (an angiotensin converting enzyme inhibitor) was administered. In the second group, 1.5 mg/kg IV of propranolol (a beta-blocker) was administered. The third group was the control. IOP and blood pressure (BP) were measured by manometry. The perfusion pressure was calculated by the difference between BP and IOP (BP-IOP). The parameters were studied at 6 moments (0, 10, 30, 60, 90 and 120 minutes). Results: There was significant reduction of IOP (p<0.05) with captopril and propranolol, without difference between the drugs. With captopril the BP and PP decreased markedly at 10 and 30 minutes. With propranolol there was no reduction of BP or PP. Conclusions: Captopril and propranolol reduced IOP. However, the marked reduction of BP, and consequently of PP caused by captopril may be undesirable for irrigation of the optic nerve.
Effect of drugs used in the treatment of arterial hypertension on intraocular pressure: Experimental study in dogs
Keywords: Captopril/therapeutic use; Dogs; Glaucoma; Hypertension/drug therapy; Intraocular pressure/drug effects; Propranolol/therapeutic use